2007
DOI: 10.3892/ijo.30.4.927
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, immunogenicity and safety of bivatuzumab mertansine, a novel CD44v6-targeting immunoconjugate, in patients with squamous cell carcinoma of the head and neck

Abstract: The prodrug bivatuzumab mertansine (BIWI 1) is a novel CD44v6-targeting humanized monoclonal antibody coupled to the toxin mertansine. In a phase I dose escalation trial 31 patients with squamous cell carcinomas of the head and neck were treated with doses of 25-325 mg/m 2 as a 30-min infusion. Thirteen patients received a second infusion after 3 weeks. Serial serum samples were collected to determine the pharmacokinetic parameters of the prodrug BIWI 1 and of deconjugated BIWI 1 as well as the occurrence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…However, CD44 is endogenously expressed at low levels in healthy tissues; 17 because of this expression, side effects still occur. 18,19 Antibody targeted therapies are effective in cancer treatments for three principal reasons: (1) The epitope recognized by the antibody is over-expressed on the tumor cell. (2) The antibody has better access to the tumor than to normal tissues that also express the epitope.…”
Section: Targeting To Cd44 With Anti-cd44 Antibodies or Hyaluronanmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CD44 is endogenously expressed at low levels in healthy tissues; 17 because of this expression, side effects still occur. 18,19 Antibody targeted therapies are effective in cancer treatments for three principal reasons: (1) The epitope recognized by the antibody is over-expressed on the tumor cell. (2) The antibody has better access to the tumor than to normal tissues that also express the epitope.…”
Section: Targeting To Cd44 With Anti-cd44 Antibodies or Hyaluronanmentioning
confidence: 99%
“…44 Anti-CD44 antibodies as targeting ligands for either radio-labels or anti-cancer chemotherapeutics in squamous cell carcinoma (SCC) of the head and neck (Table 2) stabilized disease progression in several patients. 18,19 A number of monoclonal antibodies capable of targeting SCC were identified. 45 The most specific antibody was developed as a clinical radioisotope carrier by converting it to a human/ mouse chimera that had a slightly lower half-life in circulation but a much higher capacity for cell lysis in a mouse xenograft tumor model.…”
Section: A Anti-cd44 Antibody Conjugatesmentioning
confidence: 99%
“…But new strategies and targeted therapy have been explored in the attempt to enhance survival rates in advanced HNSCC and especially unresectable HNSCC. Various experimental approaches have been investigated, as for example CD44v6 as a potential new target in HNSCC (7). Countless epigenetic and genetic events, including the aberrant expression and function of regulators of cell cycle, growth and signaling, motility, angiogenesis, and apoptosis are involved in pathogenesis of HNSCC and thus might be plausible targets for therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, various studies have suggested potential prognostic values for p53 mutations, enhanced expression of epidermal growth factor (EGFR), transforming growth factor (TGF) ·, or cyclin D1 (4)(5)(6). More recently, novel CD44v6 targeting humanized antibodies were coupled to toxic substances in order to improve response rates in HNSCC (7).…”
Section: Head and Neck Squamous Cell Carcinoma (Hnscc)mentioning
confidence: 99%
“…For example, various studies have suggested potential prognostic values for p53 mutations, enhanced expression of epidermal growth factor (EGFR), transforming growth factor-α (TGF-α) or cyclin D1 (4-6). More recently, novel CD44v6 targeting humanized antibodies were coupled with toxic substances in order to improve response rates in HNSCC (7,8).…”
Section: Introductionmentioning
confidence: 99%